The acquisition of language from a formal perspective: functional categories in children's grammar and the incidence of linguistic input (Quintú Quimün. Revista de lingüística, 2022)
The study of language acquisition occupies a central place in the theoretical framework of Generative Grammar since it attempts to answer The Logical Problem of Language Acquisition, that is, how a linguistic knowledge as complex as a mother tongue is acquired quickly and only from positive evidence. From a formal perspective, it is proposed that language acquisition is biologically determined and that grammatical knowledge is the result of a specific linguistic system. In particular, it analyses the role played by the innate language faculty in the process of language acquisition and the extent to which the structures produced by a child obey the principles of Universal Grammar. In this article, we focus on the relevant factors involved in the process of acquiring a native language and their relation to the parameterization process, on the stages through which the child's grammar passes, and on the classical hypotheses that have been proposed to explain the behavior of functional categories in children´s grammar. In addition, the results of some studies on the acquisition of Spanish, in contexts with less and more linguistic variation in the input, are presented in order to evaluate the effects of this possible variation in the development of their language.